Awareness Regarding Health Insurance Policy Scheme of Government of Nepal among Local Residents of Dharan Sub-Metropolitan City - Thapa, Roshni; Lamsal, Shyam; Badhu, Angur; Shrestha, Sharmila (Journal of BP Koirala Institute of Health Sciences, 2021)
Background: An expensive care discourages people from using health services. The health insurance policy scheme of the government of Nepal aims to provide quality health care services without a financial burden to its citizens. We aimed to assess its awareness among local people of Dharan and also find its acceptance and association with various demographic variables. Methods: This cross-sectional study was conducted among 249 households in 5 wards of Dharan sub-metropolitan city. Using a semi-structured questionnaire, a face-to-face interview was taken either from the financial decision maker/ financial supporter of the family. The socio-demographic characteristics, awareness and perception towards the health insurance policy scheme and its acceptance were assessed. The chi-square test was used to find the association of their awareness with different demographic variables. Results: The majority (70.7%) of the families were aware of the health insurance policy scheme. The most frequent source of knowledge was their friends/ family members (43.7%) followed by insurance service providers (32.4%). Only 36.6% of the families were enrolled in the health insurance policy scheme while 34.1% were not enrolled despite their knowledge about the scheme. Elderly (> 60 years), dependent, those without formal education, or those living below the poverty line were less aware regarding the health insurance policy (p < 0.05). Conclusion: About 29% of families had no idea about health insurance policy scheme and 34.1% were not enrolled in it despite being aware of the scheme. Friends/ family members and insurance service providers were common sources of information.